Cathepsin K Expression in Castration-Resistant Prostate Carcinoma: A Therapeutical Target for Patients at Risk for Bone Metastases. Issue 2 (April 2017) - Munari, Enrico; Cima, Luca; Massari, Francesco; Bertoldo, Francesco; Porcaro, Antonio Benito; Caliò, Anna; Riva, Giulio; Ciocchetta, Elisa; Ciccarese, Chiara; Modena, Alessandra; Iacovelli, Roberto; Sava, Teodoro; et al.
Background: The lysosomal cysteine protease cathepsin K is involved in bone remodeling and is also expressed in the peritumoral stroma of carcinomas arising from different organs. A new generation of cathepsin K inhibitors blocking the RANKL/RANK pathway are being developed. We sought to investigate cathepsin K expression in a cohort of castration-resistant prostate carcinomas. Methods: Sixteen cases of castration-resistant disease with at least 5 years of follow-up were selected from a cohort of 280 patients who underwent surgery. Cathepsin K was evaluated on formalin-fixed and paraffin-embedded tissue microarrays with 5 tissue spots per case. These were scored as high 2+ (≥30% of cells), low 1+ (<30% of cells) or zero (absence), distinguishing tumor cells and peritumoral stroma cells. Low (1+) and absence (0) of scoring were interpreted as negative, and high (2+) as positive. Results: The castration-resistant group was composed of 15 acinar adenocarcinomas and 1 neuroendocrine carcinoma, and all showed at least Gleason score 8 at prostatectomy. Two out of 16 cases (12%) scored positive for cathepsin K in tumor cells; and 5 of 16 cases (31%) scored positive in peritumoral stroma cells. The neuroendocrine and acinar subtypes of carcinoma with positive immunoexpression in neoplastic cells developed bone metastases after 4 and 5 years, respectively, and subsequently died. Conclusions: Patients affected by castration-resistant prostate carcinoma may be tested for cathepsin K, and a positive strong expression (2+) could be a useful predictive biomarker of response to targeted agents, aiding in the selection of patients eligible for these treatments.